(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk S, Saensouk P. 2021. Pollen morphology of subfamily Malvoideae (Malvaceae sensu lato) in Thailand. Biodiversitas 22: 5633-5643. The pollen morphology of 19 species with eight variants and ten genera of subfamily Malvoideae (Malvaceae sensu lato) were investigated by light and scanning electron microscopy. The pollen was monad, spheroidal shaped and 45.64-168.00 µm in size. The pollen grains of all species were pantoporate. All pollen had radial symmetry and were apolar. The spines pollen grain of the subfamily Malvoideae in Thailand can be divided into six types. The arrangement of spines on pollens in this study can be divided into two groups. The pollen had various exine sculptures (granulate, microreticulate, and subpsilate). Spines were found to be echinate, baculate, and spinule. Pollen size, aperture, exine sculpture and spine index can be used as characters to identify the subfamily Malvoideae species. Therefore, a key to the 19 species with eight variants and ten genera of subfamily Malvoideae in this study based on pollen morphology was provided. Eight species were studied for their pollen morphology for the first time.